DESIGN AND CONSTRUCTION OF WELL WATER FILTERIZATION EQUIPMENT AND MONITORING CLEAN WATER QUALITY IN IOT BASED BOARDING HOUSES - Saputra, Gede Andrean Yudi; Desnanjaya , I Gusti Made Ngurah; Ekayana, Anak Agung Gde; Ariana, Anak Agung Gede Bagus; Sudiarsa, I Wayan (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Water is a vital necessity for human life; however, the quality of water, particularly from wells, is often threatened by contamination such as domestic waste, agricultural chemicals, and pathogenic bacteria. To address this, this study develops a well water quality monitoring and filtration system based on the Internet of Things (IoT). This system enables real-time monitoring of water quality and automatic filtration, with data accessible through an Android application to ensure that safe and clean water is available for residents. The system was tested using three main sensors: pH, TDS, and turbidity. The pH sensor recorded an average accuracy of 96.51% with values ranging from 6.1 to 6.7, while the TDS sensor had an accuracy of 98.19% with values between 601 and 690 ppm. The turbidity sensor detected turbidity levels between 2.1 and 5.5 NTU. The filtration system operates automatically based on the detected parameters, keeping the water safe. Water quality data is displayed on an LCD and sent in real-time to the Android application, making it easy for users to monitor water conditions. It is hoped that, with broader implementation, this system can improve the health and quality of life of the residents.